Estimation of the account receivable's duration (case study JSC « Severeleсtro») - Bogatova K. A. (Interactive science, 2017)
keywords: account receivable; turnover ratio; maturity date.
Keywords: дебиторская задолженность; коэффициент оборачиваемости; срок погашения